Enta ra norma común de l’aragonés escrito: una endrezera plena de barzals - Francho Nagore Laín (Lengas)
In the written Aragonese of the Middle Ages there was no common norm, neither in writing nor in morphology, but there were some trends. These did not fully take hold when, at the beginning of the 16th century, writing in Castilian became widespread in Aragon. The few texts in Aragonese that we know from the 17th-19th centuries are quite influenced by the spelling of Spanish, a path that continues in the writings in local dialects in the 20th century. The movement to recover and dignify Aragonese that began around 1970 calls for the use of its own common spelling, and also a convergent model in morphosyntax, something that some, from the predominant dialectal mentality, only reluctantly accept. From the last thirty years of the 20th century progress is also made in the codification and selection of the lexicon. However, that process is not yet complete. The events that occur already in the s. XXI, especially since 2010 until now, have not only stopped it, but have caused a setback and even a small chaos, which the writers try to avoid despite the adversities and the brambles that are found along the way.